The Effect of Profitability, Liquidity, and Company Size on Dividend Policy with Managerial Ownership as a Moderating Variable (An Empirical Study of Commercial Banks Listed on the Indonesia Stock Exchange for the Period 2020–2024) - Virgia Putri Bhayangkari (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
This study examined the effect of profitability, liquidity, and company size on dividend policy, with managerial ownership as a moderating variable, in commercial banks listed on the Indonesia Stock Exchange (IDX) for the 2020–2024 period. The study was motivated by inconsistent dividend behavior observed across banks during a dynamic economic period marked by the COVID-19 pandemic and subsequent recovery. Using a quantitative descriptive-associative method with purposive sampling, the study selected 10 banks as samples, resulting in 50 panel data observations. Data analysis was conducted using panel data regression with EViews 12, with the random effects model (REM) selected as the estimation approach. Classical assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation tests, were conducted, and the results met the required assumptions. Moderated regression analysis (MRA) was used to test the moderating role of managerial ownership. The results indicate that profitability, measured by return on assets (ROA), has a significant positive effect on dividend policy, measured by the dividend payout ratio (DPR), whereas liquidity, measured by the loan-to-deposit ratio (LDR), and company size do not significantly affect dividend policy when tested individually. Simultaneously, the three independent variables significantly influence dividend policy, explaining 19.26% of its variation. Regarding the moderating effect, managerial ownership significantly weakens the relationship between profitability and dividend policy but does not moderate the effects of liquidity and company size on dividend policy. These findings contribute to the agency theory literature in the context of Indonesian banking and provide practical guidance for management and investors in formulating evidence-based financial decisions.